소방공무원에서 정신 건강 증진 프로그램의 효과 - 김재준; 최태영; 김소연; 박주현; Kim, Jae Jun; Choi, Tae Young; Kim, So Yeun; Park, Ju Hyun (Anxiety and mood, 2017)
Objective : The purpose of this study was to investigate the effectiveness of the mental health improvement program in Korean firefighters. Methods : A total of 502 firefighters working at Daegu, Ulsan and Gumi participated in the mental health improvement program for an 8-week period. The program included evaluation and counseling as well as psychoeducation for mental health awareness. Subjects were divided to two groups including the PTSD high risk group and PTSD non-high risk group. Results : The program resulted in a significant decrease in mean scores of depression and insomnia for all firefighters. PTSD high risk group showed a significantly higher level of depression, anxiety, and insomnia. Multiple logistic regression analysis with PTSD high risk group as a dependent variable indicated that moderate depression was a high-risk factor for PTSD in firefighters, as compared to no depression ; in addition, subthreshold and moderate insomnia was another risk factor. Conclusion : The evaluation and management of psychopathologies including depression and insomnia associated with traumatic events can be helpful to improve the mental health of firefighters.